Emotional and behavioural difficulties of children and young people at entry into care - Joe Sempik; Harriet Ward; Iain T. Darker (2008)
Emotional and behavioural difficulties of a sample of children and young people were identified at the point of entry to local authority care by analysis of social work case files. The files indicated high levels of need, including that in children aged under 5. Bedwetting was identified as an important issue related to the physical health and emotional well-being of looked-after children. There was an association between bedwetting and emotional and behavioural problems. Analysis of placement types at entry to care showed that significantly more boys than girls were first placed in residential care.